Endovascular repair of isolated post-traumatic subclavian artery false-aneurysm (FA) using gore viabahn vbx-balloon-expandable (BE) stent-graft: case report and literature review - Perri, Marco; Timpani, Carmine; Capoccia, Laura; Bianchi, Giampaolo; Balzano, Rosario Francesco; Popolizio, Teresa; Pennelli, Anna Maria; Guglielmi, Giuseppe; D'Elia, Marcello; Filauri, Pietro (Acta Biomedica Atenei Parmensis, 2022)
True and false aneurysms (FA) of the subclavian artery are at high risk of rupture due to their localization and proximity/closeness to the articular bone structures of the upper thoracic outlet and shoulders. Surgical and endovascular treatments are good options to avoid complications such as aneurysms rupture, thrombosis and distal embolism alone or in combination. Self-expandable (SE) covered stents are the most used devices for the treatment of subclavian artery aneurysms. We report on a case of post traumatic left intra-thoracic subclavian artery FA treated using endovascular technique, highlighting the usefulness of the new covered Gore Viabahn VBX-BE stent-graft that combines the advantages of a high radial strength of a BE stent with the deliverability and conformability of a SE stent.